2012
DOI: 10.4236/wja.2012.22012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Physicians in Diagnosing HIV and AIDS-Related Death in the Adult Population of Addis Ababa, Ethiopia

Abstract: Background: The lack of cause of death information is the main challenge in monitoring the effectiveness of interventions aimed at reducing HIV and AIDS-related deaths in countries where the majority of deaths occur at home. Objective: To evaluate the accuracy of physician reviewers of verbal autopsies in diagnosing HIV and AIDS-related deaths in the adult population of Addis Ababa, the capital of Ethiopia. Methods: This study was done within the context of a burial surveillance system in Addis Ababa. Trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The specificity of VA in diagnosing non-HIV deaths among those who were HIV negative was 81 percent (29 non-HIV deaths out of 36 HIV negative persons). These findings are consistent with previous studies which have shown that verbal autopsies are considerably valid in detecting HIV deaths especially among adults though underestimation of HIV deaths is not uncommon [43-45]. Generally, the accuracy of verbal autopsies interpreted by physicians is said to have an acceptable level of diagnostic accuracy, at the population level, if sensitivity and specificity are at least 50 percent and 90 percent respectively [46].…”
Section: Discussionsupporting
confidence: 91%
“…The specificity of VA in diagnosing non-HIV deaths among those who were HIV negative was 81 percent (29 non-HIV deaths out of 36 HIV negative persons). These findings are consistent with previous studies which have shown that verbal autopsies are considerably valid in detecting HIV deaths especially among adults though underestimation of HIV deaths is not uncommon [43-45]. Generally, the accuracy of verbal autopsies interpreted by physicians is said to have an acceptable level of diagnostic accuracy, at the population level, if sensitivity and specificity are at least 50 percent and 90 percent respectively [46].…”
Section: Discussionsupporting
confidence: 91%
“…In countries where registration of vital events is incomplete(inaccurate) and the proportion of people who die at home without medical care is high, verbal autopsy (VA) is used to identify causes of death [3] , [4] , [5] , [7] , [8] , [9] and measure patterns of causes of death [10] . Several studies showed that VA can be used to generate reasonable population level estimates of causes of death [11] , [12] . Thus, the VA method is recommended to obtain a population level estimate of causes of deaths in the absence of a medical recording system [4] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The AIDS Impact Module (AIM) within Spectrum was used for this analysis (version 4.50). The software is described in detail elsewhere (39). Here, we provide a brief description of how the software works and how it was adjusted to create a Nairobi-specific model.…”
Section: Methodsmentioning
confidence: 99%